Dendro-provenancing of Arctic driftwood. (15th April 2017) - Hellmann, Lena; Tegel, Willy; Geyer, Jan; Kirdyanov, Alexander V.; Nikolaev, Anatoly N.; Eggertsson, Ólafur; Altman, Jan; Reinig, Frederick; Morganti, Sandro; Wacker, Lukas; Büntgen, Ulf
Abstract: Arctic driftwood may represent a cross-disciplinary proxy archive at the interface of marine and terrestrial environments, which will likely gain in importance under future global climate change. Circumpolar network analyses that systematically consider species-specific boreal origin areas, transport routes and deposition characteristics of Arctic driftwood, are, however, missing. Here, we present tree-ring width (TRW) measurements of 2412 pine, larch and spruce driftwood samples from Greenland, Iceland, Svalbard, the Faroe Islands, and the Lena Delta in northeastern Siberia. Representing the largest Arctic driftwood TRW compilation, these data are compared against 495 TRW reference chronologies from the boreal forests of Eurasia and North America. The southern Yenisei region is the main source for recent pine driftwood at all Arctic sampling sites, whereas spruce mainly originates in western Russia and central Siberia, as well as in northern North America. Larch driftwood is, for the first time, dendro-provenanced to central and eastern Siberia. A new larch driftwood chronology extends the middle Lena River reference chronology back to 1203 CE. Annually resolved radiocarbon measurements further date six larch driftwood chronologies between 1294 and 2013 CE. Although being highly replicated, our study emphasizes the importance of interdisciplinary research efforts including radiocarbon dating, isotopic tracing and aDNA processing for improving Arctic driftwood provenancing in space and time. If successful, Arctic driftwood studies will contribute to the reconstruction of past boreal summer temperature variations and ocean current dynamics, as well as changes in sea ice extent and relative sea level over the last centuries to millennia. Highlights: We show considerable cross-dating improvement of Arctic driftwood based on the so far largest record of tree-ring data. The main species Scots pine, larch and spruce are dated and origin areas reflect the boreal forest species distribution. Most logged Scots pine timber originate in central Siberia, while spruce comes from Siberia and also from North America. Larch is dendro-provenanced for the first time mainly to eastern Siberia and is dating back to the early 13th century. Radiocarbon dating of certain samples is applied to get further insight in the temporal distribution of driftwood samples.